The role of participation in memorable tourism experience: a comparative case of cap go meh festival and linggarjati festival in Indonesia - Agus W Soehadi; Eka Ardianto (Journal of Economics, Business, and Accountancy Ventura, 2019)
The study aimed to analyze the role of participation in creating memorable tourism experience in Cap Go Meh festival and Linggarjati festival to create loyal visitors. This study used a questionnaire of 42 questions on 5-point Likert-scale ranged from one to five range (1 = strongly disagree up to 5= strongly agree) to the festival visitors after the event. The data were analyzed using Structural Equation Modelling (SEM) with Confirmatory Factor Analysis (CFA) and the structural model using regression analysis. It showed that the visitors have different motives to attend and take a part in the festival. The group socializationhas a positive effect on participation, which lead to immersion, then influences vivid memory and loyalty in Cap Go MehÂ  while novelty has a positive effect on participation in Lingarjati vestival, which lead to immersion, then influences vivid memory and loyalty. Practicaly, it implied that this study has the benefit for event manager to understand the visitors characteristics. Cap Go Meh festival can be higher in group socialization. Event manager should facilitate visitors to participate as a group on God Statue parade. In Linggarjati, the visitors gain the novelty of historical site and city history merge with the stage of angklung -traditional music instrument- colossal.